Evaluation of Delayed Neuronal and Axonal Damage Secondary to Moderate and Severe Traumatic Brain Injury Using Quantitative MR Imaging Techniques - Mamere, A.E.; Saraiva, L.A.L.; Matos, A.L.M.; Carneiro, A.A.O.; Santos, A.C. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Traumatic brain injury (TBI) is a classic model of monophasic neuronal and axonal injury, in which tissue damage mainly occurs at the moment of trauma. There is some evidence of delayed progression of the neuronal and axonal loss. Our purpose was to test the hypothesis that quantitative MR imaging techniques can estimate the biologic changes secondary to delayed neuronal and axonal loss after TBI.MATERIALS AND METHODS: Nine patients (age, 11–28 years; 5 male) who sustained a moderate or severe TBI were evaluated at a mean of 3.1 years after trauma. We applied the following techniques: bicaudate (BCR) and bifrontal (BFR) ventricle-to-brain ratios; T2 relaxometry; magnetization transfer ratio (MTR); apparent diffusion coefficient (ADC); and proton spectroscopy, by using an N-acetylaspartate/creatine (NAA/Cr) ratio measured in normal-appearing white matter (NAWM) and the corpus callosum (CC). The results were compared with those of a control group.RESULTS: BCR and BFR mean values were significantly increased (P ≤ .05) in patients due to secondary subcortical atrophy; increased T2 relaxation time was observed in the NAWM and CC, reflecting an increase in water concentration secondary to axonal loss. Increased ADC mean values and reduced MTR mean values were found in the NAWM and CC, showing damage in the myelinated axonal fibers; and decreased NAA/Cr ratio mean values were found in the CC, indicating axonal loss.CONCLUSIONS: These quantitative MR imaging techniques could noninvasively demonstrate the neuronal and axonal damage in the NAWM and CC of human brains, secondary to moderate or severe TBI.